PENGARUH SALES PROMOTION VOUCHER DISKON MELALUI MEDIA SOSIAL INSTAGRAM @BROSISDEAL TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DI MERCHANT LOKAL PEKANBARU - Nofrika Belisa; Rumyeni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Sales promotion that have the form of discount voucher or discount coupon is usually a discounted coupon distributed through advertising and can be used in certain stores only. Coupon guarantees certain savings on selected or selected products when it’s indicated as points on purchase. One of the discount vouchers is brosisdeal. Brosisdeal discount voucher contains discount from various merchants in Pekanbaru. This Brosisdeal discount voucher is promoted through social media instagram. Currently, instagram is the one of popular social media so the promotion of brosisdeal discount vouchercan lead to consumer purchasing decisions. The theory used in this research is S-R theory. The purpose of this research is to determine there is any influence sales promotion discount vouchers through social media brosisdeal’s instagram to consumer purchasing decisions at local merchants Pekanbaru.The method used is explanative quantitative using random sampling technique and the number of samples as much as 267 respondents. Researchers collected data with questionnaires. To find out there is any influence between variable X and variable Y, researcher use simple linear regression analysis. To process the test questionnaire data is done by using SPSS program Windows version 23.Based on the results of simple linear regression gets the value of regression coefficient in this research is Y = 12.884 + 0.495 X with a significance level of 0.000. Of course it’s smaller than α = 0.05. Its means that there is influence sales promotion vouchers discount through social media brosisdeal’s instagram to consumer purchasing decisions at local merchant Pekanbaru by 19% and classified as very weak category of influence. Although not dominant but respondents pay attention to the contents of the message delivered and purchase decisions arise. So, Ho is rejected and Ha accepted.Keywords: Sales Promotion, Voucher Discount, Purchasing Decision